The Influence of Personality and Chronotype on Distance Learning Willingness and Anxiety among Vocational High School Students in Turkey - Randler, Christoph; Horzum, Mehmet Barış; Vollmer, Christian (International Review of Research in Open and Distributed Learning, 2014)
There are many studies related to distance learning. Willingness and anxiety are important variables for distance learning. Recent research has shown that anxiety and willingness towards distance learning are moderated by personality. This study sought to investigate whether distance learning willingness and distance learning anxiety are associated with age, gender, occupation, chronotype and personality in a Turkish vocational high school students sample. Two measures of individual differences were implemented: chronotype (morningness/eveningness preference) and BIG-5 dimensions (agreeableness, conscientiousness, extraversion, neuroticism, and openness). Seven hundred and sixty-nine vocational high school students from Turkey filled out a self-administered questionnaire. Evening types, older, and female students had higher distance learning willingness scores than morning types, younger, and male students. No significant difference was found between chronotype groups with respect to distance learning anxiety. Furthermore, extraverted students reported a lower distance learning anxiety. Openness to experience was associated with high distance learning willingness. We conclude that evening types may benefit from distance learning more than other types.